Service of Documents in the Serbian Criminal Proceedings: Efficiency in the Gap Between Wishful Thinking and Bad Habits - Kolaković-Bojović, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
One of the few issues on which there is general consensus in the national scientific and professional community is that the inefficiency of the delivery of documents in criminal proceedings is one of the key factors of its excessive length. The reasons for this, one might say, lie at the same time in the procedural and standards on the organisation of the judiciary, since they are both outdated and ineffective. For unclear reasons, the legislature as well as the judiciary have resisted for decades to take over solutions that in other legal systems provide exceptional results, even after they have been implemented in our judiciary, acting the same way. Changes made in the framework of the process of delivery by adopting the Code of Criminal Procedure of 2011, it seems, instead of going in the direction of eliminating the root causes of the inefficiency of delivery, actually significantly narrow the rights of the accused in this area, opening up space for speed but not the efficiency of delivery.